2010
DOI: 10.1007/s11099-010-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

Induction by drought of crassulacean acid metabolism in the terrestrial bromeliad, Puya floccosa

Abstract: In the terrestrial bromeliad, Puya floccosa, a value of carbon isotopic composition (δ 13 C) of -22‰ has been previously reported, suggesting the operation of weak and/or intermediate (C 3 -CAM) crassulacean acid metabolism (CAM). In order to characterize the operation of CAM in P. floccosa and its possible induction by drought, plants were grown in Caracas and subjected to four independent drought cycles. Additionally, since plants of this species grow in Venezuela in a large range of elevations, leaf samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
1
11
0
1
Order By: Relevance
“…(1996) Talinum triangulare 6.0FacultativeHerrera et al . (1991) Puya floccosa 6.2FacultativeHerrera et al . (2010) Sedum morganianum 13.0ConstitutiveKluge and Ting (1978)…”
Section: Discussionmentioning
confidence: 99%
“…(1996) Talinum triangulare 6.0FacultativeHerrera et al . (1991) Puya floccosa 6.2FacultativeHerrera et al . (2010) Sedum morganianum 13.0ConstitutiveKluge and Ting (1978)…”
Section: Discussionmentioning
confidence: 99%
“…[88] showed more nocturnal CO 2 fixation by Bromelia humilis in the presence of nitrogen and higher irradiance. On the other hand, it was also demonstrated that another species, Puya floccosa, is capable of increasing nocturnal acid accumulation in response to drought and/or other unfavorable microclimatic cues [92]. Working with Achmea magdalenae, Bromelia plumieri and Ananas comosus, Skillman and cols.…”
Section: Type II Bromeliadsmentioning
confidence: 99%
“…It is important to note that extreme care should be taken when performing such analyses to use best practice in terms of model calibration and sampling methodology. Herrera et al, 2010;Quezada, Zotz & Gianoli, 2014). First, the putative phylogenetic relationships used in this analysis are not consistent with those supported by the most comprehensive molecular phylogenetic analyses.…”
Section: Introductionmentioning
confidence: 66%
“…CAM-cycling, thought to be the least evolutionarily advanced state along the CAM continuum (Silvera et al, 2010), involves nocturnal fixation of respiratory CO 2 behind closed stomata accompanying typical diurnal C 3 fixation. In many cases, CAM-cycling andidling appear to be reversibly inducible, and drought-inducible CAM has been observed in some species such as the terrestrial Puya floccosa (Linden) E.Morren ex Mez (Herrera et al, 2010). CAM-idling, conversely, is an extreme form of CAM in which the stomata remain continuously closed and the only fixation is of respired CO 2 at night.…”
Section: Photosynthetic Pathwaysmentioning
confidence: 99%